Sanfilippo Disease - Barik, Kanal Lal; Kumar, Prabhat; Ghosh, Tark Nath; De, Sangita; Basu, Samit (Journal of Nepal Paediatric Society, 2013)
Sanfilippo disease is a type of Mucopolysaccharidosis, a hereditary progressive disease caused by mutation of gene for degradation of acid mucopolysaccharides. Early detection of this rare disease would enable screening and genetic counseling for asymptomatic family members. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6117 J. Nepal Paediatr. SocVol.32(3) 2012 263-265